Hybrid‐triggered‐based H∞$$ {\mathcal{H}}_{∞ } $$ control for NCSs under DoS attacks - Wu, Jie; Li, Hengqian; Yang, Qingsheng; Zhan, Xisheng (Asian journal of control, 2025)
This essay aims to discuss hybrid‐triggered‐based control under denial‐of‐service (DoS) attacks. Firstly, DoS attacks on the network channel are considered. The impact caused by DoS attacks is taken as uncertainty of the hybrid‐triggered condition. Based on this uncertainty, a hybrid‐triggered scheme is designed to mitigate the impact on network bandwidth. Then, the safety controller with performance is obtained. Secondly, considering the influence of network‐induced delay in the network channel, a Lyapunov function that can reflect the time‐delay effect is established. On the basis of Lyapunov stability theory and the Shure complementary lemma, the cooperative design for trigger parameter and feedback gain is put forward. Finally, two examples are simulated to prove the feasibility and rationality of the control strategy.